Digital Privacy and Security: A Survey on the Modern Threat on the Digitization - Maschatak, Soumee; Raj, Chandan BR (International Journal of Computer Sciences and Engineering, 2025)
Today‟s software industry is operating on loses because of a modern threat known as Digital Piracy. Not only the software industry, various sectors of the industry like the cinematography, authors, inventers and discoverers are facing a threat wherein their work may attain a global attention without bringing them anything. A recent studies has shown that due to recent craze of digitization and the socio-economic condition, people are more inclined towards acquiring everything without even giving it time and money. This is becoming a threat to the intellectual property owners. This paper is all about understanding the factors affecting digital piracy, the types of digital piracy and the various steps and measures needed to stop the digital piracy from spreading its wings.